10 years experiences in surgical treatment of liver malignancies - Patrzałek, Dariusz; Chudoba, Paweł; Szyber, Piotr; Pawłowski, Stanisław; Polak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2000)
Between 1989 and 1998 two hundred and twelve patients were treated because of liver tumor at the Department of Vascular Surgery, Medical University in Wroclaw. Among them 108 patients (50.9%) were admitted because of liver metastases, 40 patients (18.8%) suffered from primary liver cancer (PLC) and 64 patients (30.1%) had benign liver tumor. Patients with PLC presented in 28 cases hepatocellular carcinoma, in 10 cases cholangiocellular carcinoma and remaining two patients had angiosarcoma. In more than a half of the patients with metastatic liver tumor the primary tumor was found in large bowel (68 cases). There were performed 11 right hemihepatectomies, 4 left hemihepatectomies, 11 bisegmentectomies, 15 segmentectomies, 23 non-anatomical resection and 74 exploratory laparotomies. In 14 cases of liver metastases liver resection was performed simultaneously with radical operation of primary tumor. Postoperative complications occurred in 28 patients (20.2%) and mortality rate was 13.0% (18 pateints).